Resort Danau Khayangan Di Pekanbaru Dengan Pendekatan Arsitektur Modern - Brilantio, Arzito Gagah; Firzal, Yohannes; S, Mira Dharma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Resort can be defined as a resting place for tourists who need facilities, so that tourists can do holiday activities or work at resorts. It is generally located quite far from the city center as well as being used as a resting place and providing facilities for vacation, recreation and sports. The location of the design of this resort is Khayangan Lake which is a place of tourism. Its location, which can be reached from the city of Pekanbaru, is quite far from the noise, has a beautiful natural atmosphere, the existence of small hills, and has a good view towards the lake. In designing this resort, modern architecture is used as the design theme. Modern architecture tries to leave ornaments or decorations that are not useful in building functions and emphasize functions. Modern architecture makes it possible to produce unusual forms because of the development of structural and construction technologies and the development of materials technology. In addition, modern architecture buildings are also more flowing based on the process of circulation and activity.Keyword: Modern Architecture, Lake Resort, Danau Khayangan